Norepinephrine Induces PTSD-Like Memory Impairments via Regulation of the β-Adrenoceptor-cAMP/PKA and CaMK II/PKC Systems in the Basolateral Amygdala - Liu, Xiang-Hui; Zhu, Rong-Ting; Hao, Bo; Shi, Yan-Wei; Wang, Xiao-Guang; Xue, Li; Zhao, Hu (Frontiers in Behavioral Neuroscience, 2019)
Glucocorticoids (GCs) can modulate the memory enhancement process during stressful events, and this modulation requires arousal-induced norepinephrine (NE) activation in the basolateral amygdale (BLA). Our previous study found that an intrahippocampal infusion of propranolol dose-dependently induced post-traumatic stress disorder (PTSD)-like memory impairments. To explore the role of the noradrenergic system of the BLA in PTSD-like memory impairment, we injected various doses of NE into the BLA. We found that only a specific quantity of NE (0.3 μg) could induce PTSD-like memory impairments, accompanied by a reduction in phosphorylation of GluR1 at Ser845 and Ser831. Moreover, this phenomenon could be blocked by a PKA inhibitor or CaMK II inhibitor. These findings demonstrate that NE could induce PTSD-like memory impairments by inhibiting AMPA receptor phosphorylation via regulation of the β-adrenoceptor-cAMP/PKA and CaMK II/PKC signaling pathways.